A Cohesion Metric Proposal for Object-Oriented Systems: COMIAS - Ertemel, H. Oezlem; Selcuk, Yunus Emre; Kalipsiz, Oya (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2009)
Despite inherent difficulties, measuring software quality is important because it makes evaluation and improvement of various aspects of software. In this study, a new cohesion metric named COMIAS is proposed and its first empirical validation is given. Being a structural metric, COMIAS can be used in every stage of software lifecycle.
Keywords: Cohesion; Object Oriented Metrics; Computer Science; Engineering